Canada jays, Perisoreus canadensis, use multiple context-dependent cache protection strategies. (October 2021) - Martin, R. Jeffrey; Sherry, David F.
Abstract : Food caching is a behaviour used by a variety of birds and mammals and can be an essential strategy for surviving food-scarce periods. Ensuring that cached food remains available for later recovery is critical to the fitness of caching individuals. Cache robbers, conspecific or heterospecific individuals that remove and consume food stored by the original cacher, present a unique threat to food-caching individuals. Accordingly, caching species have evolved a variety of cache protection strategies to limit the potential risk of cache robbery. We assessed these cache protection strategies in Canada jays, year-round residents of Canada and the western United States that rely on cached food to survive food-scarce winters. We evaluated caching behaviour and movement patterns of captive Canada jays in caching contexts that varied in potential risk of cache robbing: presence versus absence of a model cache robber and visual cover from the cache robber. We found that depending on perceived risk, Canada jays flexibly used a variety of nonmutually exclusive cache protection strategies including cache depression, out-of-sight caching and spacing. These cache protection strategies likely reduce the risk of cache robbing and increase the probability of caches remaining available for recovery and consumption. Highlights: Canada jays used quantity-based and location-based cache protection strategies. Cache protection strategies were modulated by potential cache-robbing threats. Visual information was prioritized in cache protection and cache site selection.